Dialog discusses pricing : an interview with dialog's president Roger K. Summit - GARMAN, N (Online (Weston, Conn.), 1990)
Roger K. Summit discusses DIALOG's approach to the issue of on-line data base pricing. The records printed out from a data base provide the added value contributed by the data base producer and the connect time is the added value contributed by the vendor (in this case DIALOG). A better method of pricing would be achieved if the data base producers' income came from displayed records whilst the vendors' income cam from the connect hours. Other pricing variations and obstacles to new pricing methods are discussed. 00 N.L.M.